Glucostasis Simulator: An Educational Tool for Visualizing Glucose-Insulin Feedback Using the Clinically Accepted Hovorka Model - Haya Noor; Nayyar Ijaz Dar; Syeda Ghina Sahar; Alina Sabeen Khalid (SEAN Institute, 2026)
Effective diabetes management requires a fundamental understanding of glucose-insulin dynamics and their regulation through physiological feedback systems. This paper presents an interactive simulation tool, developed in MATLAB App Designer and grounded in the clinically validated Hovorka model, to visualize these complex mechanisms. The simulator was tested across key clinical scenarios including baseline, hyperglycemia, and insulin dosing errors, with results demonstrating physiologically accurate glucose and insulin trajectories that confirm the model's successful implementation. To enhance its educational utility, the tool incorporates myth versus fact flashcards and dynamic visual aids. By bridging theoretical knowledge and practical insight, this work provides a foundational platform for exploring physiological control systems, with potential to inform the future development of personalized diabetes management strategies.